A Study on Thai Student-Teachers’ Online Learning Behaviors in the COVID-19 Pandemic - Bongkotkorn Supakesorn; Pongthorn Asawaniwed; Titiworada Polyiem (Journal of Educational Issues, 2024)
The COVID-19 pandemic causing severe and lethal health issues by means of contact or airborne transmission has significantly altered our normal way of life. Having regular face-to-face contact poses a great risk even with precautionary measures taken resulting in a drastic change in the realm of learning and teaching from onsite to online. Studying online has been seen as problematic and has received negative feedback, especially in the aspect of comprehensibility of lessons and unusual learning atmospheres. This negativity contributes to the changes in students’ behaviors which, as a result, significantly affects the learning outcome and academic achievements. This study, then, aims to investigate Thai student-teachers’ online learning behaviors during the pandemic and to study the relationship between Thai student-teachers’ online learning behaviors and learning achievement during the pandemic. The 118 participants, selected by the purposive sampling method, were student teachers enrolling in the Learning and Instruction course in the first semester of the 2020 academic year when the transition from onsite to online learning started. The instruments were the Learning and Study Strategies Inventory (LASSI) adopted from Weinstein and Palmer (2002) and a learning achievement test. The statistics used in the data analysis were percentage, mean score, standard deviation, and Pearson’s Correlation Coefficient. The results of the study were (1) 10 strategic learning behaviors were found to be used by student-teachers in Thailand in online learning during the COVID-19 outbreak and (2) the behaviors of information processing, motivation, concentration, and self-testing were correlated with learning achievement. The results could be implemented to develop teacher education processes and academic works in the related field.